PENGENALAN HAMA PENYAKIT UTAMA TANAMAN PALA DAN CENGKEH SERTA TEKNIK PENGENDALIANNYA DI DESA MOREKAU, KECAMATAN SERAM BARAT, KABUPATEN SERAM BAGIAN BARAT - Patty, John Alfred (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
Nutmeg and cloves are specific local superior commodities in the Maluku region. The exploitation of nutmeg and clove plants tends to be not optimal, partly because of the various constraints faced including the problem of Plant Destructive Organisms (OPT), so that the production and quality of nutmeg in Maluku have not been able to answer market needs. The purpose of this service activity is to introduce the main pests of nutmeg and cloves and how to control them to the people of Morekau Village, West Seram District, West Seram Regency. Activities are carried out in the form of: (1) counseling; (2) assistance; and (3) program evaluation. The response of the participants to this counseling activity was very good, as can be seen from the enthusiasm of the participants during this activity. Through the provision of this material, the people of Morekau Village understand and understand the main pests and diseases that attack nutmeg and cloves and their control techniques. The mentoring process carried out was able to produce new skills for the community in anticipating and controlling the emergence of disease pests that could attack nutmeg and clove plants.